Consequências da modulação farmacológica da Na+, K+ - ATPase na epilepsia induzida por pilocarpina - Freitas, Mayara Lutchemeyer de (2018)
Epilepsy is one of the most common chronic neurological diseases worldwide, and despite a variety of drugs introduced into clinical practice, one-third of patients remain unresponsive to therapies. In addition, when considering the adverse effects therapies, epilepsy comorbidities, socioeconomic costs for public health, and the need for understanding molecular mechanisms involved in the disease, we conclude that epilepsy research is of fundamental importance. Na+, K+ -ATPase (NKA) is an important enzyme in the regulation of neuronal excitability, and an interesting pharmacological target to be explored in epilepsy. Evidence indicates that impairment in NKA activity contributes to epileptic seizures in mice and in humans with epilepsy. In order to evaluate new pharmacological tools that modulate NKA activity, the present study sought to identify some effects of the DRSSAb antibody, capable of activating NKA activity, and agrin, a protein that appears to be associated with inhibitory effects on NKA, on a experimental model of epilepsy. To this purpose, male C57BL/6 mice were subjected to status epilepticus (SE) by administration of repeated low doses of pilocarpine, and after a period these animals had spontaneous and recurrent seizures. In the in vitro experiments the hippocampal slices of control and epileptic mice were treated with DRSSAb. Glucose uptake improved by approximately 30% in the slices of epileptic animals after treatment with DRSSAb. Glutamate release increased by 83% in slices from epileptic animals, and returned to levels of control animals after treatment with DRSSAb. These results were obtained without interfering with cell viability. In the in vivo experiments, the intrahippocampal administration of DRSSAb restored crossing activity in the open field test; the number of crossings decreased in epileptic animals, and returned to the levels of the control group after DRSSAb treatment. Regarding agrin, the levels of protein expression after SE in hippocampus of mice were not altered 24 hours after SE. However, 14 days after SE there was a decrease in agrin expression, followed by an 71 % increase 60 days after SE. Moreover, the intrahippocampal administration of agrin increased the susceptibility to epileptic seizures in SE animals, but not in control mice. In summary, present data support the hypothesis that DRSSAb antibody and agrin are promising therapeutic strategies in the search for new treatments for epilepsy.